2014
DOI: 10.1002/jso.23598
|View full text |Cite
|
Sign up to set email alerts
|

CC chemokine receptor 6 expression predicts poor prognosis in hepatocellular carcinoma

Abstract: CCR6 could be used as a molecular marker to predict prognosis for HCC. J. Surg. Oncol. 2014; 110:151-155. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Studies have reported that the CCL20/CCR6 axis plays a key role in the tumor-chemokine network and promotes tumor progression in HCC and CRC. This axis has been shown to stimulate cell proliferation, probably via regulating the expression of p21, p27, and cyclin-D1 [91,165], induce EMT via PI3K/AKT and Wnt/β-catenin pathways [166], and eventually, promote metastasis [167,168]. The CCL20/CCR6 network facilitates T reg activity and induces immune suppression to mediate cancer cell elimination and metastasis [34].…”
Section: Ccl20mentioning
confidence: 99%
“…Studies have reported that the CCL20/CCR6 axis plays a key role in the tumor-chemokine network and promotes tumor progression in HCC and CRC. This axis has been shown to stimulate cell proliferation, probably via regulating the expression of p21, p27, and cyclin-D1 [91,165], induce EMT via PI3K/AKT and Wnt/β-catenin pathways [166], and eventually, promote metastasis [167,168]. The CCL20/CCR6 network facilitates T reg activity and induces immune suppression to mediate cancer cell elimination and metastasis [34].…”
Section: Ccl20mentioning
confidence: 99%
“…Immunohistochemical staining was performed as previously described. 32 The scoring was done by two independent observers who were unaware of the clinical data. We separately assembled the nucleus and cytoplasm YAP1 expression according to the established rules.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…We separately assembled the nucleus and cytoplasm YAP1 expression according to the established rules. 32,33 The cytoplasmic expression of YAP1 was assessed by assigning a proportion score and an intensity score as previously described. The nuclear expression of YAP1 was scored by estimating the proportion of tumor cells with positive nuclear staining (0: none, 1: ≤10%, 2: 10% to ≤50%, and 3: >50%).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Interestingly, together with CCL20, CCR6 expression has been correlated with stage and prognosis in a variety of cancers including hepatocellular carcinoma [14, 15], colorectal carcinoma [1618], glioma [19], and non-small cell lung cancer [20], and a function for CCR6 in regulation of cancer progression has been putatively demonstrated using cell lines and xenograft models [16, 18, 21, 22]. In breast cancer, higher CCR6 expression levels were linked with tumor stage and grade [23], and incidence of metastasis to the pleura [24].…”
Section: Introductionmentioning
confidence: 99%